PEMODELAN TANAMAN JARAK PAGAR (JATROPHA CURCAS L.) BERBASIS EFISIENSI PENGGUNAAN RADIASI SURYA,KETERSEDIAAN AIR DAN NITROGEN(CROP MODELING OF JARAK PAGAR (JATROPHA CURCAS L.) BASED ON RADIATION USE EFFICIENCY,WATER AND NITROGEN AVAILABLE) - Gusti Rusmayadi; . Handoko; Yonny Koesmaryono; Didiek Hadjar Goenadi (PERHIMPI (Indonesian Association of Agricultural Meteorology), 2008)
A number of crop growth simulation models have been developed using the radiation use efficiency (RUE) concept to predict crop growth and yield in various environments. These models generally calculate daily biomass production as the product of the quantity of radiation intercepted and RUE. Besides that biomass production was deterimined by water and nitrogen available factor. So, this research was carried out to quantify the RUE, biomass and leaf area index on Jatropha under rainfall condition, four levels of nitrogen fertilizer (N) and two and three population densities (P) planted twice. The experiments used a systematic Nelder fan design with 9 spokes and 4 – 5 rings were conducted at SEAMEO-BIOTROP field experiment in 2007. Data from the first experiment were used for parameterization and calibration and the second experiment data for model validation. Based on parameterization, we found that RUE can prediction above ground biomass accumulation of Jatropha were 0.94 (r=0.83) g MJ-1 to 1.3 (r=0.75) g MJ-1. Water availability was between ψ=-30 kpa and ψ=-1.5 MPa for field capacity and wilting point, respectively. Nitrogen demand of root, stem, leaf and grain N were (Ndemr=0.75), (Ndems=0.60), (Ndeml=2.53), and (Ndemg=2.41), respectively. Validation showed that model can simulate crop growth and development of Jatropha.